Membrane cholesterol and substrate stiffness co-ordinate to induce the remodelling of the cytoskeleton and the alteration in the biomechanics of vascular smooth muscle cells. Issue 8 (5th November 2018) - Sanyour, Hanna J; Li, Na; Rickel, Alex P; Childs, Josh D; Kinser, Courtney N; Hong, Zhongkui
Abstract : Aims: Cholesterol not only deposits in foam cells at the atherosclerotic plaque, but also plays an important role as a regulator of cell migration in atherogenesis. In addition, the progression of atherosclerosis leads to arterial wall stiffening, and thus altering the micromechanical environment of vascular smooth muscle cells (VSMCs) in vivo . Our studies aim to test the hypothesis that membrane cholesterol and substrate stiffness co-ordinate to regulate VSMCs biomechanics, and thus potentially regulate VSMCs migration and atherosclerotic plaque formation. Methods and results: Methyl-β-cyclodextrin was used to manipulate membrane cholesterol content in VSMCs isolated from the descending thoracic aorta of male Sprague-Dawley rats and cultured on Type I collagen-coated polyacrylamide gel substrates with varying stiffness. Atomic force microscopy (AFM) was used to determine VSMCs stiffness and integrin-fibronectin (FN) adhesion. The alignment of submembranous actin filaments was visualized with AFM and confocal microscopy. The constriction force of rat aorta was measured ex vivo using a multi-wire myograph system. Our results demonstrated that cholesterol-depletion and substrate-softening induced a significant decrease in VSMCs stiffness and adhesion to FN, as well as cytoskeletal disorganization. In addition, the contractile force of rat aorta was reduced upon cholesterol-depletion. Cholesterol-enrichment resulted in an increase in stiffness, adhesion to FN, cytoskeletal organization of VSMCs compared with the cholesterol-depleted cells, and enhanced contractile force of rat aortas compared with the cholesterol-depleted vessel rings. Conclusion: Cell membrane cholesterol and substrate stiffness synergistically affect VSMCs elastic modulus (E-modulus) by regulating the organization of the actin cytoskeleton. Except for the 3.5 kPa gel substrate, cholesterol-depletion decreased VSMCs-FN adhesion force, adhesion loading rate, cytoskeletal orientation, and E-modulus compared with the control VSMCs. Conversely, cholesterol-enrichment significantly increased cytoskeleton orientation, stiffness, and VSMCs-FN cell adhesion force compared with both control and cholesterol-depleted VSMCs on a soft substrate. Graphical Abstract: